Efektivitas Leaflet dan Game Edukasi Powerpoint Terhadap Pengetahuan dan Sikap Tentang Pencegahan Obesitas Pada Remaja - Permana Putra, Firdy Rama; Budi Prasetyo; Agustina Puji Lestari; Arina Nurul Ihsani (JURNAL RISET GIZI, 2025)
Background: Obesity is the excessive accumulation of fat resulting from a prolonged imbalance between energy intake and energy expenditure. According to the Surakarta City Health Profile, the number of obesity cases among individuals aged 18 years and above increased to 8,889 cases in 2021, up from 5,384 cases recorded in 2020. Objective: To evaluate the effectiveness of leaflet media versus educational games using PowerPoint with hyperlinks in improving adolescents' knowledge and attitudes regarding obesity prevention. Methods: This study employed an experimental quantitative research design to examine the effectiveness of the experimental variables. A quasi-experimental design with a nonequivalent control group approach was used, in which the intervention was applied to an experimental group and compared to a control group. Data analysis was conducted using descriptive statistics and the Mann–Whitney test. Results: There was a significant difference in adolescents' knowledge between the leaflet and the PowerPoint hyperlink educational game media, with a p-value of 0.00 (< 0.05). The mean for the leaflet group was 10.13, higher than that of the PowerPoint game group, which was 8.57. However, there was no significant difference in adolescents' attitudes between the two media, with a p-value of 0.08 (> 0.05), and mean ranks of 40.31 for the leaflet group and 38.81 for the PowerPoint game group. Conclusion: Leaflet media is more effective in improving adolescents' knowledge compared to the PowerPoint hyperlink educational game. However, both media have a similar impact on enhancing adolescents' attitudes toward obesity prevention.